Integrated Quality Management to Enhance the Performance of Al Quraniyy Islamic Boarding School in Kotagajah, Central Lampung - Novi Wulandari; Mufti Surya Adli R; Siti Patimah; Andi Warisno; M. Indra Saputra (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
Education plays a crucial role in enhancing the quality of human resources within society. The aspiration for high-quality education is a common dream shared by many. When implemented effectively, Total Quality Management (TQM) can significantly contribute to improving the performance of Islamic boarding schools (pesantren). This study aims to explore the process of program development, implementation, and the factors influencing the application of TQM. A descriptive method with a qualitative approach was employed. Data were collected through interviews, observations, and documentation, involving subjects such as caregivers (pengasuh), teachers (asatidz), and administrators. The findings reveal that Al-Quraniyy Islamic Boarding School in Kotagajah, Central Lampung, designs its programs based on the fundamental principles of Total Quality Management. The implementation process, led by the pesantren leadership, involves all stakeholders contributing to the institution. The benefits of TQM application are evident in the improved performance of the teachers, which in turn positively affects the students’ achievements and the overall institutional performance. Two main categories of factors influence the implementation of TQM. First, supporting factors include the competence of the human resources (teachers and caregivers), adequate infrastructure, and strong trust and interest from the community, particularly parents. Second, inhibiting factors involve suboptimal human resources and a work culture among teachers and administrators that has not fully aligned with TQM principles.